Food Rescue Program: Reducing Urban Household Food Waste and Strengthening Community Food Security - Ilham Kurniawan; Aulia Umi Rohmatika; Fairuz Haniyah Ramadhani; Khoirista Noor Rohmah (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Urban areas face the dual challenges of food waste and household food insecurity. This community service activity aimed to reduce food waste and strengthen food security among low-income urban communities through a food rescue program implemented in KP Gembong RT 10, Surabaya, Indonesia. The activity involved three main stages: sorting of food items to ensure edibility and safety, packaging according to household needs, and direct distribution to beneficiaries. A total of 30 beneficiary families (household heads) received over 100 food packages containing dry food, beverages, snacks, powdered milk, and bakery products. Surplus food that remains fit for consumption is identified and diverted before becoming waste through a structured redistribution mechanism. The results indicate that this program effectively channels such food to vulnerable urban households, thereby reducing short-term household food expenditure and decreasing organic waste generation. The community-based approach enabled targeted and adaptive distribution, strengthening social solidarity between volunteers and residents. In conclusion, food rescue programs serve as a viable social intervention to bridge food surplus and deficit at the community level, contributing simultaneously to food security and environmental sustainability. However, structural food insecurity requires complementary long-term strategies.